2020
DOI: 10.1103/physrevlett.124.092301
|View full text |Cite
|
Sign up to set email alerts
|

Scattering Studies with Low-Energy Kaon-Proton Femtoscopy in Proton-Proton Collisions at the LHC

Abstract: The study of the strength and behavior of the antikaon-nucleon (KN) interaction constitutes one of the key focuses of the strangeness sector in low-energy quantum chromodynamics (QCD). In this Letter a unique high-precision measurement of the strong interaction between kaons and protons, close and above the kinematic threshold, is presented. The femtoscopic measurements of the correlation function at low pair-frame relative momentum of (K þ p ⊕ K −p) and (K − p ⊕ K þp) pairs measured in pp collisions at ffiffi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…For antikaons, the behaviour above threshold is only scarcely constrained by scattering experiments due to the low available statistics close to theKN threshold. But of late, new measurements above threshold have been made available exploiting correlation techniques to K − -p pairs [35], that are measured in pp collisions at the LHC by the ALICE collaboration.…”
Section: Experiments Forknmentioning
confidence: 99%
See 3 more Smart Citations
“…For antikaons, the behaviour above threshold is only scarcely constrained by scattering experiments due to the low available statistics close to theKN threshold. But of late, new measurements above threshold have been made available exploiting correlation techniques to K − -p pairs [35], that are measured in pp collisions at the LHC by the ALICE collaboration.…”
Section: Experiments Forknmentioning
confidence: 99%
“…The particle emitting source is found to be very small in pp and p+Pb collisions at the LHC [38,39], that is of the order of 1 fm. These values are evaluated by using known interactions, with pp and K + p as benchmarks [35]. and 13 TeV (right).…”
Section: Experiments Forknmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently it has been shown that hyperon-nucleon, hyperon-hyperon [18,19], and kaon-nucleon [20] interactions can be more precisely measured in proton-proton (pp) and proton-lead (p-Pb) collisions at the LHC. Indeed, small colliding systems at LHC energies lead to particleemitting sources with sizes of about 1 fm, allowing a precise test of the short-range strong interaction.…”
mentioning
confidence: 99%